Web-based new renumeration scheme (ssb) evaluation system / M. N. Mustaffa Kamal ... [et al.] - Mustaffa Kamal, M. N.; Yong, N. L.; Othman, F.; Zakaria, O. (2002)
This Web-based SSB Evaluation System is a web-based human resource evaluation or remuneration system, which has been developed to replace the current paperwork used in Human Resource Department (HRD) in UM. By providing a computerized SSB Evaluation form, the HRD can gather all the data entered by users using a user-friendly interface of SSB form instead of paper form. This will help to increase the quality and accuracy in data keeping, yet providing an up-to-date and economical way of information management. Moreover, this proposed system will provide safeguards to ensure reliability, accuracy and confidentiality of the information. It will also reduce the data storage cost and increase the efficiency of data storage. The Web-based SSB Evaluation System consists of a number of modules or sections. The modules are: Staff Section which enable staffs to fill in the SSB Evaluation forms; Supervisor Section which enables supervisor to view the record of the particular staff supervised by him/her, evaluate staff's performance and fill up the assessment part in SSB Evaluation forms; HRD Section which enables authorize staff to view the reports of evaluations and finally, the administrator's section which enables the administrator to keep track staffs who have submitted the SSB evaluation form on the selected date. The proposed system was developed by using Waterfall with Prototyping Model as the methodology for system development, JSP as web programming language, MySQL database and Tomcat as the web server.